Ashabul Kahfi Serious Game with Adaptive Recommendation System Based on Knowledge-Based Filtering and MULTIMOORA for Islamic Education - Yuniar Setyo Marandy; Fresy Nugroho; Ririen Kusumawati (Jurnal Teknologi dan Manajemen Informatika, 2025)
This study aims to develop a serious game based on the story of Ashabul Kahfi using a difficulty level recommendation system based on Knowledge-Based Filtering (KBF) and the MULTIMOORA method. This game is designed for elementary school students in the context of Islamic religious education, instilling moral and spiritual values through the narrative of the story of Ashabul Kahfi. The difficulty level in the game is adjusted to the player's profile based on age, experience, and preferences obtained through a questionnaire. The MULTIMOORA method is applied to process questionnaire data and provide adaptive and personalized difficulty level recommendations. The results of the study show that the application of this recommendation system is able to increase student learning motivation and learning effectiveness by providing challenges that are appropriate to each player's abilities. Thus, this study contributes to the development of adaptive and effective game-based learning media, particularly in improving the understanding of religious values among students.